GENETIC ANALYSIS OF MUTANTS FROM IRRADIATED COWPEA (Vigna unguiculata [L.] Walp.) SEEDS AND POLLEN (2016)
Cowpea, Vigna unguiculata, is an important human and livestock protein source in Nigeria, but its production is constrained by ravages of pests and climate change. Conventional breeding efforts used to fortify it against these constraints had resulted into its narrow genetic base. In order to overcome this challenge, other mutation procedures such as physical and chemical mutagens could be used. Nevertheless, information on gamma and ultra-violet (UV) irradiated cowpea seeds and pollen has not been adequately documented. Therefore, genetic analysis of cowpea mutants from gamma and UV irradiated seeds and pollen, respectively was investigated. Cowpea accessions seeds: IB, IB-Y1, IB-CR and IB-BPC from the University of Ibadan and IT86D-719, IT86D-1010, IT89KD-347-57 and IT90K-284-2 from International Institute of Tropical Agriculture were irradiated at 100, 200, 300, 400 and 500 Gy doses at the rate of 202 Gy/min using 60Co gamma. Pollen were irradiated for 60, 120, 180, 240, 300 and 360 minutes at 30,000μWs/cm2 UV prior to hand self-pollination using standard procedures. Radio-sensitivity of irradiated accessions were determined using seed germination (SG), seedling survival (SV), lethal dosage 50% (LD50) for SG and SV, primary leaf area (PLA) and seed set (SS) at M1 and M2 generations. The M1 of gamma irradiation (GI) and M2 of UV irradiation (UVI) treatments were advanced to M2GI and M3UV for phenotyping on field and their genetic stability confirmed at M3GI and M4UV, respectively. Genetic diversity of all mutants was determined using microsatellites. Ribulose-bisphosphate carboxylase primers were used for sequence analysis and classification of the mutants. Inheritance pattern was evaluated at M5 of gamma induced mutants (GIM) for erect-tall (ER), yellow flush (YF), four-primary leaf (FP), crinkled leaf, lettuce leaf (LL), twisted-pale leaf (TP) and burnt leaf (BL) traits. Data were analysed using descriptive statistics and Chi-square at α0.05. The M1 generation of IT90K-284-2 had 74.0% SG, while each of IB, IB-Y-1, IB-CR and IB-BPC had 20.0% SG at 500 Gy of GI. The IB, IB-Y-1, IB-CR and IB-BPC had UNIVERSITY OF IBADAN LIBRARY iii 0.0% SV each, while 50.0% was observed in IT86D-1010 and IT90K-284-2 at 400 and 500 Gy, respectively. The LD50 for SG and SV were lowest (326 and 149 Gy, respectively) in IB-Y-1 and highest (1053 and 620 Gy, respectively) in IT90K-284-2. The PLA of M1 ranged from 2.17±0.26cm2 to 5.98±0.85cm2. Low GI (100 Gy) and UVI (60min) increased SS of M1 plants. Mutant phenotypes and frequencies varied across the cowpea accessions and did not correspond to GI treatments. Ten GIM were stable at M3, whereas all UV induced mutants reverted to normal at M4. Polymorphic information content (0.51) obtained from microsatellites showed wide genetic diversity among the mutants and parental lines. The main mutant classes were insertion-deletions and point mutations. Inheritance of ER, TP, YF, FP and BN followed monogenic recessive pattern. Genetic interaction of crinkled and TP in homozygous recessive (crl crl tp tp) conditioned LL phenotype. Radio-sensitivity of cowpea to gamma irradiation varied among the accessions. Ultra-violet radiation was less potent for cowpea pollen mutagenesis and might not be effective for mutation breeding. Keywords: Cowpea radio-sensitivity, Gamma irradiated cowpea seed, Ultra-violet irradiated pollen, Mutant phenotypes, Pollen mutagenesis. Word count: 499